Coordination of Distributed Energy Resources in Microgrids : Optimisation, Control, and Hardware-In-the-loop Validation - Xu, Yan (IET energy engineering series, 2021)
A structured research overview of techniques to manage microgrids with distributed energy resources (DERs). The focus is on coordination on both temporal and spatial scales. Chapters cover mathematical models, sizing and siting of DERs, robust optimisation, distributed coordinated control, and hardware-in-the-loop tests.